Optimization of the Satintelkam Social and Cultural Unit of the Kediri Police in Preventing Conflicts Between Silat Schools - Simanjuntak, Rio Saputra (Advances in Police Science Research Journal, 2024)
Conflict between silat schools is a conflict that occurs between groups where there are many triggers, one of which is competition between groups, bad prejudices, whether personal, political or ideological behind it. This has become a disturbance to security and social order in the community, giving rise to indicators of problems in the pre-emptive efforts carried out in the activities of raising the Satintelkam Social and Cultural Unit of the Kediri Police. The research method used is a qualitative method. The data collection techniques used were interviews, observation and document study. The focus of this research is optimizing the mobilization of the Kediri police intelligence unit to prevent conflicts between silat schools. Primary data was obtained from interviews with members of the Satintelkam Social and Cultural Unit and each head of the silat college. Secondary data was obtained through reviewing documents related to the research object. The results of this research show that the promotion of the Satintelkam socio-cultural unit in preventing conflict between silat schools is still not optimal. Carrying out fundraising by waiting for public reports is considered insufficient to prevent conflicts between silat schools and intelligence activities, which are a form of pre-emptive effort.